Advanced Endoscopic Imaging for Diagnosis of Crohn's Disease. (24th November 2011) - Neumann, Helmut; Mönkemüller, Klaus; Günther, Claudia; Atreya, Raja; Vieth, Michael; Neurath, Markus F.
Abstract : Endoscopy in IBD has tremendous importance to diagnose inflammatory activity, to evaluate therapeutic success and for the surveillance of colitis associated cancer. Thus it becomes obvious that there is a need for new and more advanced endoscopic imaging techniques for better characterization of mucosal inflammation and early neoplasia detection in IBD. This paper describes the concept of advanced endoscopic imaging for the diagnosis and characterization of Crohn's disease, including magnification endoscopy, chromoendoscopy, balloon-assisted enteroscopy, capsule endoscopy, confocal laser endomicroscopy, and endocytoscopy.